INCREASE THE EFFECTIVENESS OF USING A VEIN (World Economics and Finance Bulletin, 2022)
This article discusses the consistent measures taken in the republic in recent years to reform agriculture and introduce market mechanisms into the industry. It is recommended to introduce a system of wider use of households of the population of the Samarkand region to increase the volume of grape production.
Keywords: importer; driver; expert; grapes